2019
DOI: 10.1111/ger.12399
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life and satisfaction of edentulous patients using conventional complete dentures and implant‐retained overdentures: An umbrella systematic review

Abstract: Background Loss of teeth has a negative influence on essential oral functions. It is important to understand edentulous patients’ perceptions about the impacts of treatment options on their oral health‐related quality of life (OHRQoL) and satisfaction. Aims To appraise the systematic reviews (with/without meta‐analysis) that investigate the impacts of complete conventional dentures (CCDs) and/or implant‐retained overdentures (IRODs) on the oral health‐related quality of life (OHRQoL) and satisfaction among ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 35 publications
1
45
0
8
Order By: Relevance
“…A systematic review reported a similar phenomenon, concluding that for patients satisfied with their CCD, IOD therapy did not add a substantial amount of satisfaction 30 . Another systematic review concluded that IOD therapy has the highest positive impact if patients demand such a therapy 31 …”
Section: Discussionmentioning
confidence: 90%
“…A systematic review reported a similar phenomenon, concluding that for patients satisfied with their CCD, IOD therapy did not add a substantial amount of satisfaction 30 . Another systematic review concluded that IOD therapy has the highest positive impact if patients demand such a therapy 31 …”
Section: Discussionmentioning
confidence: 90%
“…The outcome of the OHRQoL is in accordance with earlier published papers. All papers indicate the superiority of an implant-supported overdenture compared to a conventional complete denture regarding the quality of life [ 32 , 33 , 34 , 35 ]. Moreover, a recent published paper investigating the difference in OHRQoL between patients with an implant fixed complete denture and patients with an implant overdenture could not find a significant difference in OHIP score between the two treatment groups [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of teeth has a negative influence on essential oral functions (Sharka et al, 2019). Immediate denture is a viable and important rehabilitation method to reestablish the patient's self-esteem, comfort, esthetics and function, and should be well planned and fabricated to achieve the best results (Goiato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%